Species, Age-Pattern And Other Epidemiological Features Of Caprine Coccidial Infection In Hulu Langat, Selangor - Abu, Jalila (1994)

(untitled)
Eimerian oocysts were found in 89% of 815 faecal samples from goats of smallholders in Selangor area. Nine species of Eimeria identified (and their prevalence of infection) were E. arloingi (71 %), E. ninakohlyakimovae (67%), E. christenseni (63%),E. alijevi (61 %), E. hirci (34%), E. jolchijevi (22%), E. caprovina (12%) E. caprina(9%) and E. pallida (4%). The mean opg was significantly (p<0.05) higher in the age group less than 16 weeks. Faecal samples where the counts were in the range of 10,000- 100,000 and above 100,000 was also high in this age group. After this age, the mean opg generally decreased . The mean opg in the age group less than 16 weeks was high due to the presence mainly of nonpathogenic species.No clinical coccidiosis was found probably because of E. ninakohlyakimovae (the most pathogenic species) being present in low counts throughout the study period. Age of kids, sunshine and hygiene were significantly related to oocyst counts.